PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI DEALER SENTRAL MOTOR YAMAHA CABANG SUKABUMI - Dwi Rachmawati; Gelaria Yaumal Akbar; Udriyah Udriyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Promotion is a way for a company to have a role to inform, persuade, andremind potential customers of products that are created to create a demand. Thepurchase decision is a decision that is influenced by several factors that will makeconsumers consider everything and in the end consumers buy the brand they likethe most. This research aims to see how a person's decision to buy a product is seenfrom the promotion made by a company for its product. This study examines theeffect of promotion on product purchase decisions at Dealer Sentral Motor YamahaSukabumi Branch. The results showed that promotion has a close relationship withpurchasing decisions, furthermore promotion has a significant positive effect onpurchasing decisions. This indicates that if promotion increases, purchasingdecisions will also increase.